Unlucky versus coincidence: Dual hepato-pancreatico biliary diagnoses in a six-year-old - Beth M. Campbell; Craig A. McBride; Jonathan W. Fawcett (Elsevier, 2016)
We describe a case of inflammatory myofibroblastic tumor presenting as a head of pancreas mass in a six-year-old girl. The etiology of such lesions is elusive, with a poorly understood malignant potential. One hypothesis is that they occur in areas of inflammation and trauma. The tumor occurred two years after this same patient had a Type I choledochal cyst excised with Roux-En-Y hepaticojejunostomy.